Relationship Between Time of Admission, Help-Seeking Behavior, and Psychiatric Outcomes: “From Dusk Till Dawn” - Knorr, Marius; Hofmann, Andreas B.; Miteva, Dimitrina; Noboa, Vanessa; Rauen, Katrin; Frauenfelder, Fritz; Seifritz, Erich; Quednow, Boris B.; Vetter, Stefan; Egger, Stephan T. (Frontiers in Psychiatry, 2022)
Introduction Day and time of admission influence treatment outcomes and prognosis in several medical specialties; this seems related to resources' ability. It is largely unknown whether this also applies to mental health services. We investigate the relationship between time of admission, patients' demographic and clinical profile, and treatment outcomes. Methods Demographic and clinical profiles of admitted and discharged patients to a general psychiatric ward between January 1st, 2013 and December 31st, 2020, were analyzed. In addition, we used the last year (i.e., 2020) to monitor rehospitalization. Time of admission was defined as weekdays (working day, weekend) and dayshifts (daytime, dusk, and dawn). Results During the study period, 12,449 patient admissions occurred. The mean age of the sample was 48.05 ± 20.90 years, with 49.32% (n = 6,140) females. Most admissions (n = 10,542, 84%) occurred on working days. Two-fifths of admissions (39.7%, n = 4,950) were compulsory, with a higher rate outside daytime hours. Patients had slight differences in the clinical profile, resulting from evaluating the different items of the Health of Nation Outcome Scale (HoNOS). Patients admitted on night shifts, weekends, and holidays showed a shorter length of stay; patients compulsorily admitted during daytime (disregarding the day of the week) had a longer length of stay. All patient groups achieved a robust clinical improvement (i.e., an HoNOS score reduction of around 50%), with similar readmission rates. Discussion The main finding of our study is the relationship between “daytime hours” and fewer compulsory admissions, a result of the interplay between demographics, clinical characteristics, and out-of-clinic service availability (such as ambulatory psychiatric- psychological praxis; day-clinic; home-treatment). The differing clinical profile, in turn, determines differences in treatment selection, with patients admitted after office hours experiencing a higher rate of coercive measures. The shorter length of stay for out-of-office admissions might result from the hospitalization as an intervention. These results should encourage the implementation of outpatient crisis-intervention services, available from dusk till dawn.